A new method to estimate risk and return of non-traded assets from cash flows the case of private equity funds - Driessen, Joost 1974-; Lin, Tse-Chun; Phalippou, Ludovic 1976- (National Bureau of Economic Research, 2008)
"We develop a new GMM-style methodology with good small-sample properties to assess the abnormal performance and risk exposure of a non-traded asset from a cross-section of cash flow data. We apply this method to a sample of 958 mature private equity funds spanning 24 years. Our methodology uses actual cash flow data and not intermediary self-reported Net Asset Values. In addition, it does not require a distributional assumption for returns. For venture capital funds, we find a high market beta and significant under-performance. For buyout funds, we find a low beta and no abnormal performance, but the sample is small. Larger funds have higher returns due to higher risk exposures and not higher alphas. We also find that Net Asset Values significantly overstate fund market values for the subset of mature and inactive funds"--National Bureau of Economic Research web site